Teachers’ Digital Competences: An Overview on Technological Perspectives - Meylina Meylina; Lidwina Sri Ardiasih; Rahmiaty Rahmiaty (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2021)
The Covid-19 pandemic has shifted educational systems all over the world. As a result, the employment of technology continues to be controversial, and the debate over whether English teachers actually use technology to boost their talents continues. What amount of digital literacy is imparted by their educational experience, and if they adequately equipped with digital capabilities to meet their daily needs is still arguable. Thus, the demand toward the improvement of digital media is linked to digital literacy, which subset of digital competence. Along with same line, teachers need to evaluate their readiness to integrate technology in teaching processes. Today, Universitas Terbuka (UT) provides a critical chance for English teachers to help their students develop their English abilities in complicated scenarios like as the Covid-19 pandemic. Hence, the purpose of this study is to assess the digital skills of English teachers and to describe their preparation for and response to the Covid-19 pandemic. In achieving this study's goals, 8 online tutors and 17 students of Online English Department of UT participated in the study. To obtain the data, questionnaire and interview were used to explore the importance of teacher’s readiness in teaching English, particularly on teachers’ technological competence. The SWOT Analysis was also be analyzed to capture the strengths, weaknesses, opportunities, and threats on teacher’s readiness in digital competencies. The results of this study inform decision-makers at UT and the other similar higher education institutions using similar platforms and who may have the same concerns.